Hubungan Kompetensi Instruktur dengan Hasil Belajar Peserta Pelatihan Pengolahan Ikan Air Tawar - Dzisye, Humaira; Rosmilawati, Ila (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
In the process, learning to instruct instructors as teachers is the creator of learning conditions in which the instructor is responsible for the education of the learners. Therefore, the instructor should have a good level of competence in carrying out his duties as a teacher either pedagogical competence, personality competence, professional competence and social competence. With this competence, it is expected that the instructor can motivate the students to learn better, so that the expected learning result is a satisfactory achievement. The purpose of this research is to know the correlation of pedagogic competence, personality competence, professional competence and social competence of instructor in improving the learning result of freshwater fish processing trainees at LKP Sanggar Budaya An-Nahdlah in Pandeglang. The research approach used in this research is quantitative research with research method used in this research is using non experiment method. This research is a correlation research, because it aims to test the influence or correlation between several research variables and to identify predictive relationships using correlation techniques or more sophisticated statistical techniques. The results obtained that, (1) the level of competence of instructors in LKP Sanggar Budaya An-Nahdlah Pandeglang according to the distribution of data obtained in the level enough with a large percentage of pedagogic competence of 87.2%, personal competence of 76.6%, professional competence of 79.3%, and social competence 80.0%. (2) there is a relationship between instructor's competence (pedagogic, personality, professional, and social) in improving learning outcomes.